Expanding the molecular versatility of an optogenetic switch in yeast - Figueroa, David; Baeza, Camila; Ruiz, Diego; Inzunza, Claudia; Romero, Andrés; Toro, Rodrigo; Salinas, Francisco (Frontiers in Bioengineering and Biotechnology, 2022)
In the budding yeast Saccharomyces cerevisiae, the FUN-LOV (FUNgal Light Oxygen and Voltage) optogenetic switch enables high levels of light-activated gene expression in a reversible and tunable fashion. The FUN-LOV components are encoded in two different plasmids, which includes identical promoter and terminator sequences, restricting its genome integration by homologous recombination and future applications in wild and industrial yeast strains. In this work, we expand the molecular versatility of the FUN-LOV switch, permitting its functionality in a wine yeast strain. Initially, we generated new variants of this system by replacing the promoter and terminator sequences and cloning the system in a single plasmid (FUN-LOVSP; Single Plasmid). Furthermore, we included the nourseothricin (Nat) and hygromycin (Hph) antibiotic resistances in FUN-LOVSP (FUN-LOVSP-Nat and FUN-LOVSP-Hph), permitting its selection after genome integration. Then, we compared the levels of light-activated expression for each FUN-LOV variants using the luciferase reporter gene in the BY4741 yeast strain. The results indicate that FUN-LOVSP-Nat and FUN-LOVSP-Hph, either episomally or genome integrated, reached higher levels of luciferase expression upon blue-light stimulation compared the original FUN-LOV system. Finally, we demonstrated the functionality of FUN-LOVSP-Hph in the 59A-EC1118 wine yeast strain, showing similar levels of reporter gene induction under blue-light respect to the laboratory strain, and with lower luciferase expression background in darkness condition. Altogether, we developed new FUN-LOV variants for light-mediated transcriptional activation, which are functional in a wine yeast genetic background, expanding the versatility and applicability of this optogenetic tool.